Automated peritoneal dialysis in urgent‐start dialysis ESRD patients: Safety and dialysis adequacy. Issue 3 (9th November 2022) - Jin, Haijiao; Lv, Shifan; Wang, Ling; Zhang, Minfang; Wang, Qin; Fang, Wei; Lin, Xinghui; Che, Xiajing; Yan, Hao; Yu, Zanzhe; Jiang, Na; Li, Zhenyuan; et al.
Abstract: Background: Recent evidence suggests that automated peritoneal dialysis (APD) might be a feasible alternative to hemodialysis (HD) in urgent‐start peritoneal dialysis. Methods: This prospective study enrolled end‐stage renal disease (ESRD) patients who had started APD as an urgent‐start dialysis modality at a single center. Dialysis‐related complications were recorded. Dialysis adequacy and electrolytes imbalance were compared between baseline, 14 and 42 days after catheter insertion. Technique survival and patient survival were also recorded. Results: A total of 36 patients were included in the study. Mean follow‐up duration was 22 months. During the follow‐up, 11 PD patients (30.6%) developed dialysis‐related complications. Only two patients (5.6%) required re‐insertion and one patients (2.8%) transfer to HD. The 2‐year technique survival rate and patient survival rate were 94.4% and 97.2%, respectively. Conclusion: In considering safety and dialysis adequacy, APD could be a feasible dialysis modality for urgent‐start dialysis in ESRD patients, using a standard procedure.